Perumusan Strategi dengan Pendekatan Blue Ocean Strategy pada PT Alpha Beta Charlie (ABC) - Imam F Arief; Haris Maupa (Universitas Tarumanagara, 2021)
The research objective is to design and formulate alternative strategies using the Blue Ocean Strategy approach for PT Alpha Beta Charlie to maintain the stability of operational activities to achieve the company’s vision and mission. The Blue Ocean Strategy challenges companies to get out of the red ocean of coal mining contractor competition by creating a new market space that makes competition becomes irrelevant. In conducting the Blue Ocean Strategy analysis, four stages of the analysis tool are used, TOWS Analysis, Canvas Strategy, Four Action Framework, and Eliminate-Reduce-Raise-Create Grid (ERRC Grid). Furthermore, the output/proposed strategy will be tested with the Blue Ocean Idea (BOI) Index to measure the feasibility of the resulting strategy. The primary data used in this study came from interviews with decision-makers. As secondary data used internal data/company reports. Based on TOWS Analysis, SO strategy is obtained, which means using internal strengths to take advantage of existing opportunities. Strategy reformulation was carried out by synthesizing the proposed strategy (SO) with the Blue Ocean Strategy which resulted in seven new strategy items that have met the rules of the Blue Ocean Idea (BOI) Index in terms of Buyer Utility, Price, Cost, and Adoption for PT Alpha Beta Charlie. The new proposed strategy is expected to take the company out of the red ocean competition with its competitors. Tujuan penelitian adalah merancang dan merumuskan strategi alternatif dengan menggunakan pendekatan Blue Ocean Strategy untuk PT Alpha Beta Charlie untuk menjaga kestabilan kegiatan operasional guna mencapai visi dan misi perusahaan. Blue Ocean Strategy menantang perusahaan untuk keluar dari samudra merah persaingan kontraktor penambangan batu bara dengan menciptakan ruang pasar baru yang membuat persaingan menjadi tidak relevan. Dalam melakukan analisis Blue Ocean Strategy, digunakan empat tahapan alat analisis yaitu Analisis TOWS, Canvas Strategy, Four Action Framework, dan Eliminate-Reduce-Raise-Create Grid (ERRC Grid). Selanjutnya usulan strategi akan diuji dengan Indeks Blue Ocean Idea (BOI) untuk mengukur kelayakan strategi. Data primer yang digunakan dalam penelitian ini berasal dari wawancara kepada pengambil keputusan diperusahaan. Sebagai data sekunder digunakan data internal / laporan perusahaan. Berdasarkan Analisis TOWS diperoleh strategi SO yang artinya menggunakan kekuatan internal untuk memanfaatkan peluang yang ada. Reformulasi strategi dilakukan dengan mensintesis usulan strategi (SO) dengan strategi samudra biru yang menghasilkan tujuh item strategi baru yang memenuhi kaidah Indeks Blue Ocean Idea (BOI) dalam hal Utilitas Pembeli, Harga, Biaya, dan Adopsi untuk PT Alpha Beta Charlie. Strategi baru yang diusulkan diharapkan dapat membawa perusahaan keluar dari persaingan samudra merah dengan para pesaingnya.